Effect of seepage on the penetration resistance of bucket foundations with bulkheads for offshore wind turbines in sand. (15th May 2018) - Zhang, Puyang; Wei, Wei; Jia, Nan; Ding, Hongyan; Liu, Run
Abstract: A bucket foundation with bulkheads (BFB) is a new form of offshore foundation that is divided into seven compartments by an internal skirt and bulkheads. Suction penetration is an important process during the installation of BFBs. However, little attention has been paid to the effect of seepage on the penetration resistance of BFBs in sand. In this paper, a series of experiments and numerical simulations are performed to study the seepage field and the effect of seepage on the penetration resistance of a BFB during suction installation in sand. Moreover, a method of calculating the penetration resistance of BFBs is proposed considering the seepage effect, and the penetration resistance distribution of the BFB test model is analyzed. The analysis results show that seepage obviously reduces the penetration resistance of BFBs, and the ratio of reductions in resistance to the total resistance reaches a maximum value of 0.55 at the final penetration stage. In addition, the soil resistance of the bucket wall is significantly larger than those of the internal skirt and bulkheads for the BFB model. Highlights: The seepage field and the effect of seepage onthe penetration resistance of a BFB during suction installation in sand. The ratio of reductions in resistance to the total resistance reaches a maximum value of 0.55 at the final penetration stage. The soil resistance of the bucket wall is significantly larger than those of the internal skirt and bulkheads of the BFB.